Very low probability of significant liver inflammation in chronic hepatitis B patients with low ALT levels in the absence of liver fibrosis. Issue 8 (4th September 2020) - Sonneveld, Milan J.; Brouwer, Willem P.; Hansen, Bettina E.; Chan, Henry L.‐Y.; Piratvisuth, Teerha; Jia, Ji‐Dong; Zeuzem, Stefan; Chien, Rong‐Nan; Choi, Hannah; de Knegt, Robert J.; Wat, Cynthia; Pavlovic, Vedran; et al.
Summary: Background: Guidelines recommend liver biopsy to rule out significant inflammatory activity in chronic hepatitis B (CHB) patients with elevated hepatitis B virus (HBV) DNA but without other indications for treatment. Aim: To study rates and determinants of clinically significant liver inflammation. Methods: We selected patients with HBV DNA > 2000 IU/mL from the SONIC‐B database. The presence of significant inflammation (METAVIR ≥ A2 or HAI ≥ 9) was assessed by liver biopsy and correlated with alanine aminotransferase (ALT) levels (according to AASLD upper limits of normal [ULN]) and stratified by the presence of significant liver fibrosis (Ishak ≥ 3 or METAVIR ≥ F2). Results: The cohort included 2991 patients; 1672 were HBeAg‐positive. ALT was < ULN in 270 (9%), 1‐2 times ULN in 852 (29%) and > 2 times ULN in 1869 (63%). Significant fibrosis was found in 1419 (47%) and significant inflammatory activity in 630 (21%). Significant inflammatory activity was found in 34% of patients with liver fibrosis, compared to 9.5% of those without ( P < 0.001). Among patients without fibrosis, significant inflammatory activity was detected in 3.6% of those with normal ALT, 5.0% of those with ALT 1‐2 times ULN and in 13% of those with ALT > 2 times ULN ( P < 0.001). ALT < 2 times ULN had a negative predictive value of 95% for ruling out significant inflammatory activity among patients without liver fibrosis. Conclusions: Among patients without significant fibrosis, an ALT level < 2 times ULN is associated with < 5% probability of significant inflammatory activity. If fibrosis can be ruled out using non‐invasive methods, liver biopsy solely to assess inflammatory activity should be discouraged.